Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.3390/ijms20112635
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Walled Carbon Nanotube-Induced Gene Expression Biomarkers for Medical and Occupational Surveillance

Abstract: As the demand for multi-walled carbon nanotube (MWCNT) incorporation into industrial and biomedical applications increases, so does the potential for unintentional pulmonary MWCNT exposure, particularly among workers during manufacturing. Pulmonary exposure to MWCNTs raises the potential for development of lung inflammation, fibrosis, and cancer among those exposed; however, there are currently no effective biomarkers for detecting lung fibrosis or predicting the risk of lung cancer resulting from MWCNT exposu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 38 publications
(54 reference statements)
0
17
0
Order By: Relevance
“…The association of activating RTK mutations, giving enlarged sensitivity and disease response to RTK inhibitors, permitted the development of new approaches for the personalized treatment of lung cancer. The comprehensive epigenetic, genomic and molecular characterization of lung cancer has guided the identification of novel targeted therapies based on natural or synthetic small molecules [5,8]. The major risk factors for lung cancer, like smoking tobacco and exposure to chemical carcinogens, are sustained by an unhealthy inflammatory diet (low consumption of fruits and vegetables and high salt consumption [9]).…”
Section: Introductionmentioning
confidence: 99%
“…The association of activating RTK mutations, giving enlarged sensitivity and disease response to RTK inhibitors, permitted the development of new approaches for the personalized treatment of lung cancer. The comprehensive epigenetic, genomic and molecular characterization of lung cancer has guided the identification of novel targeted therapies based on natural or synthetic small molecules [5,8]. The major risk factors for lung cancer, like smoking tobacco and exposure to chemical carcinogens, are sustained by an unhealthy inflammatory diet (low consumption of fruits and vegetables and high salt consumption [9]).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that exposure to CNTs can have toxic effects through the generation of oxidative stress or by inducing inflammation [ 18 ]. MWCNT and SWCNT are two important classes of CNTs, and their underlying mechanisms of toxicity have been investigated using RNA-Seq.…”
Section: Carbon Nanotubesmentioning
confidence: 99%
“…A previous study in 2014 investigated the correlation and concordance of MWCNT-induced gene expression in vitro monoculture and co-culture of human small airway epithelial cells (SAEC) and human microvascular endothelial cells (HMVEC) with gene expression in vivo mouse lung exposed to MWCNT. Snyder-Talkington et al compared MWCNT-induced mRNA gene expression from human SAEC and HMVEC in monoculture and coculture [ 18 , 22 ]. When HUMVEC were cocultured and treated with MWCNTs, there were more concordant genes (both up- or downregulated in vivo and in vitro) than those of monoculture, particularly disease-related concordant genes [ 19 , 22 ].…”
Section: Carbon Nanotubesmentioning
confidence: 99%
“…84 Also, the changes in mRNAs and miRNAs predicted to indicate pulmonary fibrosis in individuals exposed to MWCNTs. 85 As a result, by the advent of CNTs in the field of lung cancer detection, another way was opened in the aspect of the efficiency of these nanotubes in medicine (Figure 3). Besides, the alteration of micro RNAs and RNAs of cancerous cells was acquirable with CNTs.…”
Section: Using Carbon Nanotubes In Lung Cancer Detectionmentioning
confidence: 99%